Activities of Military Topographers in Western Siberia in Foreign and Domestic Policy of the Russian Empire in 19th Century - Evgeny V. Igumnov (Научный диалог, 2020)
The activities of military topographers in Western Siberia to provide cartographic information on the foreign and domestic policies of the Russian Empire in Central Asia and Siberia in the 19th century are considered in the article. The role of information in the formation of the Russian Empire is emphasized. The contribution of the state to the organization of the study of the Asian regions of Russia and neighboring countries is noted. The establishment of the military topographic service in Western Siberia can be traced taking into account data on administrative transformations in the Siberian region, and on changes in the foreign policy of the Russian Empire. The participation of military topographers in determining and designating the state border with China is described in detail. The question of the role of military topographers in the scientific study of China and Mongolia is raised. The significance of the activities of military topographers for the policy of the Russian Empire on the socio-economic development of Siberia and the north-eastern part of the territory of modern Kazakhstan is revealed. The contribution of topographers to the construction of the Trans-Siberian railway, the design of river channels and new land routes is revealed. A large amount of literary sources, materials on the work of military topographers of Western Siberia, published in “Notes of the Military Topographic Department of the General Staff” is used in the article.